Time to stop upper gastrointestinal studies for pyloric stenosis - Pillai, Mrinal S.; Mohanty, Pankaj Kumar (International Journal of Contemporary Pediatrics, 2016)
We refer to the case series on pyloric stenosis.1 The authors selected 25 of IHPS patient prospectively with data regarding history, examination, operation and full follow up with time. In the study, 48% of patients had no signs of dehydration, 36 % had no electrolyte abnormalities, and none had urinary pH abnormality. With widespread availability of health care, late presentation of pyloric stenosis is less common. More babies present early with one or fewer days of vomiting with no evidence of dehydration, electrolyte abnormalities or urinary paradoxical aciduria. However, sensitivity of presence of palpable pyloric mass whose sensitivity was reported to be up to 85% has reduced to 15.5% probably due to early presentation, decreasing clinical skill and increased use of imaging.